2002
DOI: 10.1002/ca.10067
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of medical students' use of Web‐based resources for a gross anatomy and embryology course

Abstract: An extensive Web site supporting our gross anatomy and embryology course, which includes various course management pages as well as online lectures, has been in use for the past 2 years. To determine how this Web site is being used by students, we examined server log files to track access to each of the Web pages on the site. Using this data, along with student responses on a course evaluation, we have been able to quantitatively characterize Web site use and gain some insight into students' perception of the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

10
51
0

Year Published

2004
2004
2017
2017

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 67 publications
(61 citation statements)
references
References 7 publications
10
51
0
Order By: Relevance
“…Advances in technology over the last decade in particular have aided this objective, with Carmichael and Pawlina (2000), for instance, demonstrating that students appreciate the use of animated PowerPoint presentations in anatomy lectures. Nieder and Nagy (2002) showed that when posted online, electronic audio-stream versions of embryology lectures (podcasts) and audiovisual podcasts (often termed screencasts) are accessed heavily by students. Other studies show that many students believe that podcasts in various formats are a useful resource for studying anatomy and related areas, especially for their own review purposes (Patasi et al, 2009;Shantikumar, 2009;Marker et al, 2010;Schreiber et al, 2010;Thapa and Richardson, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…Advances in technology over the last decade in particular have aided this objective, with Carmichael and Pawlina (2000), for instance, demonstrating that students appreciate the use of animated PowerPoint presentations in anatomy lectures. Nieder and Nagy (2002) showed that when posted online, electronic audio-stream versions of embryology lectures (podcasts) and audiovisual podcasts (often termed screencasts) are accessed heavily by students. Other studies show that many students believe that podcasts in various formats are a useful resource for studying anatomy and related areas, especially for their own review purposes (Patasi et al, 2009;Shantikumar, 2009;Marker et al, 2010;Schreiber et al, 2010;Thapa and Richardson, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…This adoption of technology into the classroom was accelerated with expansion of the Web, which elevated the level of innovation and collaboration in the development of educational applications by making it easier for faculty to author, distribute and update courseware (Candler and Blair, 1998;McNulty et al, 2000;Levine, 2002;Nieder and Nagy, 2002). The rapid increase in the development of web-based computer-aided instruction (CAI) and the availability of content databases provide easy access to educational materials that enhance a student's ability to learn.…”
Section: Introductionmentioning
confidence: 99%
“…Many institutions restructured their anatomy courses toward problem-based learning (PBL), (Chakravarty et al, 2005;Azer, 2011), team-based learning (TBL), (Neider et al, 2005;Vasan and DeFouw, 2005;Vasan et al, 2009Vasan et al, , 2011, self-directed learning (Misch, 2002), and CAL (Heylings, 2002;Turney, 2007;McNulty et al, 2009). These changes resulted in the use of prosected specimens and multimedia equipment that, in turn, led to a decrease in time spent on cadaver dissection (Aziz et al, 2002;Nieder and Nagy, 2002;Parker, 2002;Trelease 2006). There seems to be an ongoing debate on when and how to teach anatomy (Dinsmore et al, 1999;Fitzgerald et al, 2008;Bergman et al, 2011).…”
mentioning
confidence: 96%